The creep behaviour of fibre reinforced plastics - Dootson, M. (College of Aeronautics, 1969)
Synopsis: This paper describes the tensile creep behaviour of fibre reinforced plastics under a uniaxial stress system. In particular, unidirectionally and bidirectionally reinforced plastics are considered for the relative ease with which samples of them can be manufactured. A composite model that has previously been described 1, 2 is used as the basis of theoretical predictions of the variation of the creep compliance with certain material parameters. The parameters whose effects are examined are the volume fraction of the fibres, the distribution of fibre orientations, and the angle between a specified direction and the direction of application of a uniaxial stress system. Specimen experimental results are included to show the accuracy of these predictions and any shortcomings of the theoretical model are examined in the light of this comparison.